Photopolymerization of acrylamide Initiated by the three-component system Safranine/Triethanolamine/ Diphenyliodonium chloride: The effect of the aggregation of the salt - Gómez, María L. (2004)
The effects of diphenyliodonium chloride (DPI) on the polymerization of acrylamide photoinitiated by the dye safranine with triethanolamine as a coinitiator were investigated in aqueous solutions. The salt notably increased the polymerization rate. This accelerating effects increased appreciably at concentrations of DPI at which the light scattering of the solutions became important. The effects of DPI on the photophysical properties of the dye were also investigated. Although the absorption and fluorescence were scarcely affected, the triplet yield increased by 60%. However, the polymerization rate increased by a factor much higher than that of the triplet yield. The results obtained at high concentrations of the salt could be ascribed to the presence of aggregates of the hydrophobic cations. The lower limit established for the formation of the aggregates was a DPI concentration of approximately 1 × 10 -3 M. Possible mechanisms for the action of the salt were examined.